A Case of Unilateral Pseudoglioma of Eye in A Neonate: Life Sciences-Paediatrics - Hamsa, V.S.; Jagadeeswari, S. (International Journal of Life Science and Pharma Research, 2022)
Pseudoglioma is a condition presenting as leukocoria other than retinoblastoma. Persistent hyperplastic primary vitreous is a type of pseudoglioma in an ocular developmental defect in which the hyaloid vasculature within the vitreous overgrows and fails to regress.In this case , 25 days old female child presented with the complaints of white pupillary reflex in the right eye since birth. Baby was born to second degree consanguineous parents. The child was born at full-term by normal delivery. The Antenatal period was uneventful. No history of oxygenation and birth trauma. Anterior segment examination of the right eye showed a shallow anterior chamber and leukocoria. Lens was cataractous and vascular. The left eye was normal. Examination under anesthesia revealed normal corneal diameter and Intraocular pressure in both the eyes. Fundus examination was normal in the left eye and cannot be performed in the right eye. Ultrasound B-scan in the right eye showed an echogenic band in the posterior surface of the lens and on colordoppler arterial blood flow was seen in the band. Hence, the patient was diagnosed to have Anterior persistent hyperplastic primary vitreous in the righteye.In this case ,child is advised to undergo Right lensectomy with cautery of the persistent anterior hyaloid stalk and anterior vitrectomy.